On Notifications. - Cerf, Vinton G. (Communications of the ACM, 2025)
This essay explores the nature and function of notifications across both everyday human experiences and emerging computational systems. The author argues that notifications serve a fundamental role in synchronizing otherwise asynchronous processes, whether it's boiling spaghetti or managing distributed computing tasks. As AI-driven agents become more prominent, ensuring effective and precise inter-agent communication through protocols like Agent2Agent (A2A) and Model Context Protocol (MCP) is increasingly essential. By framing notifications as critical synchronization tools, the essay invites further inquiry into how these mechanisms might be formalized within next-generation intelligent systems.